(untitled) (Journal of Nobel Medical College, 2014)
Introduction: This is a cross-sectional study with the objective of identifying modification in delivery practice in Rajbanshi mothers of Nepal. Methodology: Both qualitative and quantitative tools were used. Semi-structured questionnaires covering 375 samples of its resident districts Morang, Jhapa and Sunsari districts and check lists for in-depth interview were used in the study. Results: People were adopting both traditional and modern care practices concurrently. Among 375 households; 40% adopted local clinic/ hospital/ traditional healer concurrently. Similarly 31.20% adopted local clinic/ traditional healer/ hospital, 10.67% adopted hospital/traditional healer. There were 11.47% (urban 0.54% and rural 10.93%) respondents were having traditional care system as a first choice. During first delivery among 375 mothers 265 (70.67%) had traditional home delivery and 110 (29.33%) had hospital delivery. During last delivery, this was 115 (30.67%) in traditional home delivery and 260 (69.33%) in hospital delivery. Therefore trend of hospital delivery was increasing whereas trend of traditional home delivery was decreasing. It was statistically highly significant (p=<0.0001). There was also remarkable increased in using trained Health Worker/Nurse/Doctor at hospitals is 66.4% during last delivery which was only 6.13% during first delivery. It is statistically highly significant (p= <.0001). Conclusion: Trend of hospital delivery was increasing (from 30.67% to 69.33%) and trend of home delivery was decreasing (from 69.33% to 29.23%) in between first and last child delivery. There was remarkable increased in using trained HW/Nurse/Doctor at hospitals is 66.4% during last delivery which was only 6.13% during first delivery. Traditional care was more practiced in rural than in urban population. DOI: http://dx.doi.org/10.3126/jonmc.v3i1.10047 Journal of Nobel Medical College Vol.3(1) 2014; 10-15